ASSESSMENT OF THE RURAL POPULATION ECONOMIC ACTIVITY IN THE SYSTEM OF UNITED TERRITORIAL COMMUNITIES DEVELOPMENT: A CASE STUDY OF VOLYN REGION, UKRAINE - Oksana APOSTOLYUK; Tetiana SHMATKOVSKA; Inna CHYKALO1; Andrew HUSAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article evaluates the dynamics of the main indicators of economic activity of the rural population of Volyn region, formed and highlighted trends in their development in the region and compared with neighboring regions within the Polissya economic zone of Ukraine. Particular attention is paid to the analysis of the intensive reduction of employment of the rural population in traditional sectors of economic activity, which leads to an increase, on the one hand, rural unemployment, and on the other – to an increase in employment in personal peasant farms. The study substantiated that employment in the personal economy turned out to be more profitable for the rural population – the income per unit of labour there is now about twice as high with twice as low labour productivity. The explanation for this is the shadow nature of production in peasant farms and the imbalance of the economic mechanism in enterprises. It is substantiated that, taking into account the number of employed persons who produced products for personal consumption in private farms, programs inefficient use not only of their labour resources, but also reduces the average industry efficiency of labour resources of the agricultural sector as a whole. Among other features of the rural labour market of Volyn region, which limits its development, we can point to the non-compact distribution of the rural population in the territory. Peculiarities of the settlement network in Volyn region are that the dominant segment of rural employment is agricultural enterprises. It was found that in the current conditions it is advisable to develop and implement a set of measures to improve demographic processes, optimize employment and improve the living standards of the rural population, which requires effective cooperation between government and research institutions, relevant authorities and interested private entities. It is proved that in the rapidly changing conditions of modern times the optimization of territorial mobility of the working population between types of employment, areas of employment, insufficient and surplus areas, adaptation of statistical information base to the specifics of rural employment to rationalize economic activity and prevent negative phenomena continue to be extremely important and acute issues in Ukraine.